Phrase Depicting Immoral Behavior Dilates Its Subjective Time Judgment - Jia, Lina; Shao, Bingjie; Wang, Xiaocheng; Shi, Zhuanghua (Frontiers in Psychology, 2021)
Intuitive moral emotions play a major role in forming our opinions and moral decisions. However, it is not yet known how we perceive the subjective time of the moral-related information. Here we compared subjective durations of phrases depicting immoral-, disgust-, or neutral-behaviors in a duration bisection task, and found that phrases depicting immoral behavior were perceived as lasting longer than the neutral and disgusting phrases. By contrast, subjective duration of the disgust phrase, unlike the immoral phrase, was comparable to the neutral phrase. Moreover, lengthening effect of the immoral phrase relative to the neutral phrase was significantly correlated to observer’s anonymously prosocial tendency. Our findings suggest that immoral phrases induce embodied moral reaction, which alters emotional state and subsequently lengthens the subjective time.